The Relationship between Knowledge of Environmental Law and Its Impact on Commitment to Environmental Sustainability - Qahtani, Saad Al (Journal of Ecohumanism, 2024)
The global imperative for environmental sustainability has catalyzed a shift in societal consciousness, particularly within Western industrialized nations. This heightened awareness, coupled with a collective willingness to enact change, underscores a pivotal moment in addressing environmental challenges and fostering sustainable development. Concurrently, organizations are increasingly tasked with mitigating their environmental footprint. As such, governments, corporations, and academia have intensified their focus on environmental policies and legislation. This study investigates the relationship between environmental legislation awareness, green values (GV), perceived organizational support (POS), and their commitment to environmental sustainability (CES) in Saudi Arabia. Leveraging data from 429 gainfully employed individuals, the examined the interplay of these variables. The research contributes significantly to understanding the drivers of CES in the Saudi context, illuminating the relationships between knowledge of environmental legislation (KEL), GV, POS, and CES among employees. Through rigorous analysis, the findings unveil nuanced insights into the determinants of individual commitment to environmental sustainability. By delineating these relationships, the study provides valuable guidance for policymakers, organizational leaders, and stakeholders striving to foster environmental stewardship in Saudi Arabia and beyond.